Performance evaluation of existing sunshine-based computing models for estimating global solar radiation at Lagos, Nigeria - Nwokolo, Samuel; Ogbulezie, Julie (International Journal of Advanced Astronomy, 2017)
Several empirical models have been fitted in literature for estimating global solar radiation across the globe in order to produce global solar radiation data and also as a baseline for further scientific and environmental research without the substantial cost of instrumental network that would otherwise be needed. However, peers and researchers have reported that the most commonly employed parameter for predicting global solar radiation is sunshine duration as a result of its availability and simplicity in course of measurement globally. In this research, the author considered the performance of 63 sunshine-based models for the prediction of global solar radiation at Lagos, Nigeria. Numerous models are found unreliable for use in this location, and others vary in performance. On the whole, the best model was identified due to its values of statistical indicators.